Single tube duplex PCR for simultaneous detection of Phytophthora capsici and Radopholus similis infecting black pepper (Piper nigrum) - DINU ANTONY; SANTHOSH J. EAPEN, ARAVIND RAVINDRAN, AUNDY KUMAR* (Indian Phytopathology, 2012)
Foot rot and slow decline diseases caused by Phytophthora capsici or Radopholus similis pose major economic threat to black pepper production. The movement of pathogens and the consequent disease outbreak is largely due to latently infected plantlets and the contaminated nursery medium. One of the strategies to prevent the spread of pathogens across the different pepper growing regions is to produce and distribute disease free vigorous plantlets. A rapid and reliable single tube duplex PCR based method to detect P. capsici and R. similis in infected roots of black pepper was standardized. This method involved use of two sets of primers designed from the conserved internally transcribed spacer (ITS) region of Oomycetes pathogen, P. capsici and rDNA sequences of nematode pathogen, R. similis. The single tube duplex PCR based technology can be adopted by developmental agencies for simultaneous indexing of both these major soil borne pathogens in plantlets of black pepper aimed for public distribution and large scale transplanting.